PENGARUH RETURN ON EQUITY, NET PROFIT MARGIN DAN DEBT TO EQUITY RATO TERHADAP HARGA SAHAM - Ayu Suryo Pujilestari (2014)
In the course of stock market prices stock market is affected by many factors such as Return On Equity , Net Profit Margin and Debt to Equity Ratio so as to affect the stock market price changes. The population in this research number 45 real estate property company listed in Indonesia Stock Exchange (IDX) the period of 2008-2012. This study uses secondary data, in the form of financial statements obtained through reference to data available on the Indonesia Stock Exchange (IDX) and the website that displays data researched the company's stock price. Number of samples obtained by 10 company. The sampling method using purposive sampling techniqueThe statistical analysis used in this study is the classical assumption, regression and hypothesis testing while the coefficient of determination is a statistical method used t test and F test with a confidence level of 5 %. The results of the study showed that the t test return on equity significantly influence the stock price with a significance level of 0.000 for the variable Net Profit Margin no significant effect on the share price of 0,078 and Debt to Equity Ratio no significant effect on the stock price of 0.053. Simultaneously, return on equity, net profit margin and debt to equity ratio significantly influence the stock price with a significance value of 0.000.